Molecular characterization of Pectobacterium atrosepticum infecting potato and its management through chemicals - Hameed,Akhtar; Zeeshan,Muhammad; Binyamin,Rana; Alam,Muhammad Waqar; Ali,Subhan; Zaheer,Muhammad Saqlain; Ali,Habib; Riaz,Muhammad Waheed; Ali,Hafiz Haider; Elshikh,Mohamed Soliman; Alarjani,Khaloud Mohammed (PeerJ, 2024)
Potato farming is a vital component of food security and the economic stability especially in the under developing countries but it faces many challenges in production, blackleg disease caused by Pectobacterium atrosepticum (Pa) is one of the main reason for damaging crop yield of the potato. Effective management strategies are essential to control these losses and to get sustainable potato crop yield. This study was focused on characterizing the Pa and the investigating new chemical options for its management. The research was involved a systematic survey across the three district of Punjab, Pakistan (Khanewal, Okara, and Multan) to collect samples exhibiting the black leg symptoms. These samples were analyzed in the laboratory where gram-negative bacteria were isolated and identified through biochemical and pathogenicity tests for Pa. DNA sequencing further confirmed these isolates of Pa strains. Six different chemicals were tested to control blackleg problem in both vitro and vivo at different concentrations. In vitro experiment, Cordate demonstrated the highest efficacy with a maximum inhibition zones of 17.139 mm, followed by Air One (13.778 mm), Profiler (10.167 mm), Blue Copper (7.7778 mm), Spot Fix (7.6689 mm), and Strider (7.0667 mm). In vivo, Cordate maintained its effectiveness with the lowest disease incidence of 14.76%, followed by Blue Copper (17.49%), Air One (16.98%), Spot Fix (20.67%), Profiler (21.45%), Strider (24.99%), and the control group (43.00%). The results highlight Cordate’s potential as a most effective chemical against Pa, offering promising role for managing blackleg disease in potato and to improve overall productivity.
Keywords: Molecular characterization; Pectobacterium atrosepticum; Potato infection; Disease management; Chemical control